Laparoscopy in chronic pelvic pain - Sandoval Díaz, Ither (2015)
Chronic pelvic pain is a frequent pathology in the female population, especially in the reproductive age. Sometimes it produces disability, representing a very serious problem in gynecological practice for diagnosis and treatment. Laparoscopy is the most used microinvasive technique to treat this problem. In this paper we present the different laparoscopy procedures used in the treatment of this pathology, indications and usefulness. In our environment pelvic denervation procedures are most frequently used.